USE OF BENZOFURAN LIGNANS TO INDUCE IL-25 EXPRESSION AND SUPPRESS MAMMARY TUMOR METASTASIS - YIN SHU-YI; YANG NING-SUN; KUO YUEH-HSIUNG; CHEN YUNG-HSIANG (2018)
A method for suppressing tumor metastasis, in which an effective amount of a compound of formula (I) is administered to a subject in need thereof. Also disclosed is a method of treating cancer, in which an effective amount of a chemotherapy agent and an effective amount of a compound of formula (I) is administered to a subject in need thereof. Further disclosed are pharmaceutical compositions forsuppressing tumor metastasis and for treating cancer, each of the compositions containing a compound of formula (I). 种抑制肿瘤转移的方法，其中向有需要的个体施予有效量的式(I)化合物。本发明还公开了种治疗癌症的方法，其中向有需要的个体施予有效量的化学治疗药剂以及有效量的式(I)化合物。本发明另公开种用于抑制肿瘤转移以及治疗癌症的药物组合物，每种组合物含有式(I)化合物。